ALOKASI TENAGA KERJA PADA USAHATANI SUTERA ALAM DI DESA KRENCENG KABUPATEN KEDIRI - Aldon Sinaga; Elok Nurhiasati; Asnah Asnah; Rikawanto EM (BUANA SAINS, 2010)
This resarch aims to analyze : a) the allocations of household labor on natural silk farm, b) the contribution of labors allocation of natural silk farm on the absorption of household labors, c) factors effecting labors allocation on natural silk farm. This research conducted at the Krenceng Village, Kediri Regency used survey methode. The data analyse used descriptive statistic and multiple regression. The results of this research shows that : a) total labor used on natural silk farm activities as much as 287,70 MDE/year, b) the contribution of natural silk farm activities on household labor absorption more than 28 percent of potential household labor force, c) labor allocation on natural silk farm influenced by planting area of murbei, number of eggs, silk farm frequention and number of household members